2021
DOI: 10.3389/fgene.2021.607248
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification of miRNAs and Temperature-Responsive lncRNAs From Mango (Mangifera indica L.)

Abstract: Mango is a major tropical fruit in the world and is known as the king of fruits because of its flavor, aroma, taste, and nutritional values. Although various regulatory roles of microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) have been investigated in many plants, there is yet an absence of such study in mango. This is the first study to provide information on non-coding RNAs (ncRNAs) of mango with the aims of identifying miRNAs and lncRNAs and discovering their potential functions by interaction predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…In mango, a total of 7610 lncRNAs were identified in response to temperature changes. Notably, lnc26299 was found to have the capability to interact with related cDNA 12B (RC12B), a protein that exhibited significant upregulation in response to cold stress [ 80 ]. Additionally, Lai et al .…”
Section: Role Of Lncrnas In the Growth Development And Stress Respons...mentioning
confidence: 99%
“…In mango, a total of 7610 lncRNAs were identified in response to temperature changes. Notably, lnc26299 was found to have the capability to interact with related cDNA 12B (RC12B), a protein that exhibited significant upregulation in response to cold stress [ 80 ]. Additionally, Lai et al .…”
Section: Role Of Lncrnas In the Growth Development And Stress Respons...mentioning
confidence: 99%
“…Ptr-miR396b was determined to target 1-aminocyclopropane-1carboxylic acid oxidase ( ACO ) in response to cold stress in orange ( Poncirus trifoliata ) [ 119 ]. In mango, bioinformatic analysis reveals that MmiR78769 and MmiR101928 target phospholipase A and phospholipase D, respectively, both of which are associated with plant temperature stress-responsive process [ 120 ]. Moreover, degradome-wide analyses have revealed that miR393- TIR1 / AFB displays a cold stress-specific response and miR156- SPL -mediated heat stress response in banana [ 121 ].…”
Section: Functions Of Mirnas and Lncrnas In Fruit Responses To Biotic...mentioning
confidence: 99%
“…LncRNAs involved in the response of chilling injury in tomato fruit have been systematically identified, providing a new perspective on lncRNA roles in chilling tolerance in fruits [ 123 ]. In mango, the cold-responsive lncRNA CRlnc26299 can interact with RC12B , which is the low-temperature and salt-responsive protein [ 120 ]. A novel lncRNA, COLD INDUCED lncRNA 1 ( CIL1 ), is a positive regulator in plant response to cold stress by regulating the expression of endogenous reactive oxygen species ( ROS ) in Arabidopsis [ 124 ].…”
Section: Functions Of Mirnas and Lncrnas In Fruit Responses To Biotic...mentioning
confidence: 99%
“…Transcriptome analysis facilitated the identification of 18 eIF genes (eukaryotic elongation factor) that were expressed under salinity, osmotic and low temperature (2 °C) stress [ 49 ]. Computational analysis using EST and RNA sequence databases in mango established non-coding RNAs such as miRNAs and lncRNAs to be involved in growth and development, ripening, transcription regulation and stress responses [ 96 , 99 ] ( Table 2 ). Furthermore, bHLH TF genes and WD40 protein family members regulating abiotic stress responses in mango, citrus and papaya can provide the knowledge for understanding the responses during salt, drought, alkaline and cold stress conditions [ 50 , 51 , 71 ].…”
Section: Abiotic Stressmentioning
confidence: 99%